Contrasting efficacy of cocoa POD HUSK extract and 8% propolis extract in maintaining of root canal wall cleanliness - Tamara Yuanita; Uli Sasi Andari; Mandojo Rukmo; S. Sukaton; Deavita Dinari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: The existence of the smear layer, which can be produced during root canal instrumentation, may compromise the bond between filling material and the root canal walls. Therefore, the use of an effective root canal irrigation solution, a commonly employed form of which is sodium hypochloride (NaOCl), is important. Sodium hypochloride has several positive properties including effectiveness as a disinfectant agent and its ability to promote tissue-dissolution, although it is ineffective at cleaning the smear layer. There have been numerous recent studies of the application of phytomedicines in endodontics due to their advantages such as minimum toxicity and cost effectiveness. The saponin contained in both the propolis and cocoa pod husk acts as a surfactant that may lower surface tension and dissolve debris containing organic and anorganic materials. Purpose: The study aimed to provide evidence of the differences between root canal wall cleanliness when treated with 8% propolis extract and different concentrations of cocoa pod husk extract. Methods: 25 extracted teeth with single straight root canals were randomly divided into five categories (n=5). Sample preparation was performed using a rotary file and irrigated with different solutions. The first group was administered 2.5% NaOCl, the second group 8% propolis, the third group 3.12% cocoa pod husk extract, the fourth group 6.25% cocoa pod husk extract, and the fifth group 12.50% cocoa pod husk extract. The samples were then dissected into two sections at the apical third and their cleanliness scores subjected to a Mann-Whitney test with a significance level of p=0.05. Results: A significant difference was identified between all groups (p<0.05) and on the median control test, the highest value of 1.6 was recorded by the 6.25% cocoa pod husk extract, compared to the other four groups Conclusion: Cocoa pod husk extract demonstrates greater efficacy at cleaning root canal walls compared to 8% propolis extract.